Combining the grid‐based spatial planning and network‐based transport planning - Mesarec, Beno; Lep, Marjan (Technological and Economic Development of Economy, 2009)
Border regions of EU countries are confronted with changes of spatial and economical development. The lack of border crossing strategic information system for regional planning purposes reflects in non‐intense cooperation in the field of regional development strategies harmonization. The article presents the methodology developed during Interreg III B project REDECON. Grid‐based database with GIS interface, merging socio‐economic, environmental and spatial data with vector‐based network accessibility data, what enable the public planning departments to analyze and simulate different policy measures concerning transport. The article is focused on the modifications of (during project REDECON) developed methodology, which enable besides cross‐border spatial analysis also analysis of current status of public transport demand and supply for finding the areas, where the supply of public transport services does not reach the demand for public transport services. It describes the methodology for selecting the main indicator thematic groups for different public transport demand types, the characterization (evaluation) of suitability of locations in respect to the balance between public transport supply and demand. At the end of the article the results of methodology application are presented on the regional pilot project concerning accessibility of pilot area, regional public transport demands and regional optimization of the public transport supply.Integruotas erdvinis teritorijų ir viešojo transporto planavimas – REDECON metodikaSantrauka. Aprašoma Redecon metodika, sukurta vykdant tarptautinio projekto Interreg III B metu. Tinklelinė duomenų bazė, paremta geografinėmis informacinėmis sistemomis, suvienijo socialinius ir ekonominius, aplinkosaugos, erdvinius ir vektorinius pasiekiamumo duomenis. Visa tai leido viešojo transporto planuotojams lengviau analizuoti ir modeliuoti transporta skirtingomis priemonėmis. Straipsnyje aprašomoji sukurtos metodikos modifikacija, padedanti nagrineti transporto sistemos paklausa, parodo, kuriose teritorijose viešojo transporto aprūpinimas nepakankamas ir pan. Pabaigoje svarstoma, kokiam regionui galima pritaikyti šią metodiką, to regiono viešojo transporto paklausą ir optimizavimą.Reikšminiai žodžiai: viešasis transportas, teritorijų planavimas, geografinės informacinės sistemos.First published online: 21 Oct 2010